Zastosowanie leków przeciwhistaminowych w schorzeniach otolaryngologicznych - Buczyłko, Krzysztof (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
This study was a review of the antihistamines (AH) in allergic rhinitis (AR). Most patients had comorbid ocular symptoms, asthma and anxiety. Fifty-five percent consulting for the first time were diagnosed with AR, of whom 2/3 also had conjunctivitis and 1/3 asthma. In other study 3/4 asthma patients had AR and 1/4 did not. Every five required in the preceding year a treatment in emergency departments. The routine use of antihistamines for treating otitis exudativa in children cannot be recommended. Antihistamines were the most commonly prescribed or recommended symptomatic medicines in sinusitis (1/4 of the patients). About 30% reported sleep disturbance, increased to 44% in sedating AH (sAH) users, with reduced cognition and productivity loss. As histamine is a wake-promoting amine known to decrease during sleep, decreased histamine could mediate daytime sleepiness. Seventeen young men with AR underwent dynamic brain PET under an single dose of olopatadine (acute scan), and after repeated administration for 4 week (chronic scan). The acute scan showed a slight decrease in H(1) receptor binding potential across the cerebral cortex (by 15%), the chronic scan – a marked decrease (by 45%). 3/4 of patients taking a nonsedating AH (nsAH) plus an intranasal corticosteroid (ingcs) had moderate or severe disease. Antihistamines was the main treatment taken (nsAH in 38% and sAH in 23% of subjects). Intranasal AH therapy: use of azelastine plus ngcs is effective in both AR and nonallergic rhinitis. Olopatadine and azelastine were similarly well tolerated. The recent availability of some nsAH as over-the-counter products places them as the first-line treatment for moderate AR. Ingcs are the treatment of choice for severe form. Allergic rhinitis was treated with a AH (77%), ingcs (66%), vasoconstrictors (38%), and/or LTRA (42%). In the studies reviewed, desloratadine, fexofenadine, and levocetirizine were effective in relieving the nasal congestion. This effect began as early as day 2, was consistent and progressive throughout treatment. In children, there is favour of continuous treatment with both nsAH and ingcs for controlling symptoms during allergen exposure, but not when symptoms are negligible.